Postoperative Pain and Analgesic Requirements in the First Year after Intraoperative Methadone for Complex Spine and Cardiac Surgery - Murphy, Glenn S.; Avram, Michael J.; Greenberg, Steven B.; Shear, Torin D.; Deshur, Mark A.; Dickerson, David; Bilimoria, Sara; Benson, Jessica; Maher, Colleen E.; Trenk, Gregory J.; Teister, Kevin J.; Szokol, Joseph W. (Anesthesiology (Philadelphia), 2020)
WHAT WE ALREADY KNOW ABOUT THIS TOPICThe intraoperative administration of methadone is effective in reducing postoperative painPreventative analgesic interventions may provide protection against the development of persistent postoperative pain WHAT THIS ARTICLE TELLS US THAT IS NEWUsing data from two previously completed trials, it was observed that a single intraoperative dose of methadone was associated with fewer episodes of pain during the first month after cardiac surgery and the first 3 months after spinal surgeryFewer spine surgery patients who received methadone intraoperatively were receiving opioids 3 months after surgery, suggesting a possible reduction in chronic opioid use BACKGROUND:Methadone is a long-acting opioid that has been reported to reduce postoperative pain scores and analgesic requirements and may attenuate development of chronic postsurgical pain. The aim of this secondary analysis of two previous trials was to follow up with patients who had received a single intraoperative dose of either methadone or traditional opioids for complex spine or cardiac surgical procedures. METHODS:Preplanned analyses of long-term outcomes were conducted for spinal surgery patients randomized to receive 0.2 mg/kg methadone at the start of surgery or 2 mg hydromorphone at surgical closure, and for cardiac surgery patients randomized to receive 0.3 mg/kg methadone or 12 μg/kg fentanyl intraoperatively. A pain questionnaire assessing the weekly frequency (the primary outcome) and intensity of pain was mailed to subjects 1, 3, 6, and 12 months after surgery. Ordinal data were compared with the Mann–Whitney U test, and nominal data were compared using the chi-square test or Fisher exact probability test. The criterion for rejection of the null hypothesis was P < 0.01. RESULTS:Three months after surgery, patients randomized to receive methadone for spine procedures reported the weekly frequency of chronic pain was less (median score 0 on a 0 to 4 scale [less than once a week] vs. 3 [daily] in the hydromorphone group, P = 0.004). Patients randomized to receive methadone for cardiac surgery reported the frequency of postsurgical pain was less at 1 month (median score 0) than it was in patients randomized to receive fentanyl (median score 2 [twice per week], P = 0.004). CONCLUSIONS:Analgesic benefits of a single dose of intraoperative methadone were observed during the first 3 months after spinal surgery (but not at 6 and 12 months), and during the first month after cardiac surgery, when the intensity and frequency of pain were the greatest.